Baryon resonances in a finite volume - Meißner Ulf-G.; Rusetsky Akaki (EPJ Web of Conferences, 2017)
We review the main results obtained in the project A.6, which dealt with hadron-hadron scattering and resonances in a finite volume. These results provide tools for the extraction of the resonance characteristics from lattice QCD simulations. In particular, in this review we focus on the evaluation of the matrix elements of the weak and electromagnetic currents between the states containing at least one resonance, as well as on the description of the three-particle states in a finite volume. We also discuss insights obtained using unitarized chiral perturbation theory in a finite volume.